Hybrid System Using Two Panel Parallel Solar Cells 110 WP and PLN Power Source - Sarono Widodo (Politeknik Negeri Semarang, 2018)
The limited availability of electricity and its continued use need to was sought for savings by providing alternative energy. New renewable energy sourced from sunlight can be an energy solution for electrical energy needs. Savings can be done using hybrid techniques from two sources to supply the load. This research makes hybrid plants utilizing sunlight using two panels of 110 wp capacity solar cells installed parallel to get a large output current. In this hybrid system used a deep cycle 12v / 100 Ah battery to supply 100-250 watts of light for three to four hours. The test results show that battery charging is very dependent on solar radiation and is needed for seven hours to reach 88% capacity and the inverter supplies a load of 213.5 watts on average for 45 minutes requiring 20% of battery capacity.